The Alpaca Melanocortin 1 Receptor: Gene Mutations, Transcripts, and Relative Levels of Expression in Ventral Skin Biopsies - Bathrachalam Chandramohan; Carlo Renieri; Vincenzo La Manna; Antonietta La Terza (The Scientific World Journal)
The objectives of the present study were to characterize the MC1R gene, its transcripts and the single nucleotide polymorphisms (SNPs) associated with coat color in alpaca. Full length cDNA amplification revealed the presence of two transcripts, named as F1 and F2, differing only in the length of their 5′-terminal untranslated region (UTR) sequences and presenting a color specific expression. Whereas the F1 transcript was common to white and colored (black and brown) alpaca phenotypes, the shorter F2 transcript was specific to white alpaca. Further sequencing of the MC1R gene in white and colored alpaca identified a total of twelve SNPs; among those nine (four silent mutations (c.126C>A, c.354T>C, c.618G>A, and c.933G>A); five missense mutations (c.82A>G, c.92C>T, c.259A>G, c.376A>G, and c.901C>T)) were observed in coding region and three in the 3′UTR. A 4 bp deletion (c.224 227del) was also identified in the coding region. Molecular segregation analysis uncovered that the combinatory mutations in the MC1R locus could cause eumelanin and pheomelanin synthesis in alpaca. Overall, our data refine what is known about the MC1R gene and provides additional information on its role in alpaca pigmentation.